ANALISIS PENGEMBANGAN UMKM BERBASIS WAKAF UANG DI KOTA BENGKULU - Asnaini, Asnaini (Institut Agama Islam Bengkulu, 2018)
The spirit of waqf institutionalization (waqf managed by the government) is to maximize the benefits of waqf assets for people's welfare. Bengkulu City has the potential for large cash waqf. Bengkulu city has a high opportunity to develop waqf-based SMEs. Management of cash waqf to advanceSMEs can be carried out with a scheme to maximize the role of mosque worshipers actively. Jamaah can act as Wakif (JW), Nadhir (JN), Beneficiaries (JPM), and as Trustees or Supervisors (JPP). The starting point is the mosque congregation. With this scheme the development of waqf-based SMEs for mosques or what the authors call 'kaFUangMas' can be started, namely from pilgrims to worshipers. This scheme requires shared enthusiasm and commitment. Sense of brotherhood and caring and the desire to move forward together. Honing, caring and fostering each other in achieving prosperity and justice.